Implementasi Mesin Computer Numerical Control Berbasis Android pada Industri Mebel Pasuruan Untuk Meningkatkan kapasitas Produksi - Rosita Dwi Ferdiani Ferdiani; Wahyudi Harianto; Sri Wilujeng; Muchamad Hengki Riawan Putra; Heri Santoso (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2025)
Randusari is one of the sub-districts in Pasuruan City. Randusari is known as one of the centers of the furniture industry in Pasuruan City. This community service aims to increase the production capacity of UD. Sumber Urip furniture through the Implementation of Android-Based CNC Machines. This community service was carried out because of problems from UD. Sumber Urip in the form of a lack of production tools in the form of carving machines, resulting in carving work using manual tools that are ineffective in terms of time and energy. The solution to this problem is the provision of an android-based CNC machine that functions as a carving machine and cutting machine. The method used in this community service is a workshop on machine use and mentoring and monitoring of success which is held once a month. The results of this community service are a.) UD Sumber Urip gets additional production tools so that it can increase production capacity. b). Increasing UD. Sumber Urip's knowledge in operating android-based CNC machines. c). Increasing UD. Sumber Urip's knowledge in maintaining CNC machines.